The Integration of Qur'an Value in Technical Efficiency of Onion Business: Data Envelopment Analysis (DEA) Approach - Sri Hindarti; Titis Surya Maha Rianti; Arief Joko Saputro (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
The high productivity of onions is determined by the efficiency of farmers in using farm inputs. This study attempts to forecast onion production trends and technical efficiency levels. This study was conducted in Tawangagro Village, Karangploso District, Malang, East Java. The research data used primary data from as many as 40 onion farmers—data analysis using the Variable Return to Scale (VRS) and input-oriented Data Envelopment Analysis technique. The findings demonstrated the technical inefficiency of onion farming operations, with an average technical efficiency value assuming a CRS of 0.78 and an average technical efficiency value taking a VRS of 0.951. Associated with the Qur'an in the context of agriculture, the verse emphasizes that farmers should use inputs not excessively so that it causes waste in terms of capital or the use of input factors for their farming. There are 15 farmers with an efficiency scale of onion farmers (SE) equal to one, meaning that 37.5% of farmers are already farming with a constant return to scale, and 62.5% of other farmers are farming with an increasing scale of returns Farmers that have not been productive should change how they use their inputs to increase their efficiency. Thus the productivity of onion farming can also increase. To increase productivity, farmers should have an effective consultation helps to improve TE.